Perinatal morbidity and mortality in early‐onset fetal growth restriction: cohort outcomes of the trial of randomized umbilical and fetal flow in Europe (TRUFFLE). (23rd September 2013) - Lees, C.; Marlow, N.; Arabin, B.; Bilardo, C. M.; Brezinka, C.; Derks, J. B.; Duvekot, J.; Frusca, T.; Diemert, A.; Ferrazzi, E.; Ganzevoort, W.; Hecher, K.; et al.
ABSTRACT Objectives Few data exist for counseling and perinatal management of women after an antenatal diagnosis of early‐onset fetal growth restriction. Yet, the consequences of preterm delivery and its attendant morbidity for both mother and baby are far reaching. The objective of this study was to describe perinatal morbidity and mortality following early‐onset fetal growth restriction based on time of antenatal diagnosis and delivery. Methods We report cohort outcomes for a prospective multicenter randomized management study of fetal growth restriction (Trial of Randomized Umbilical and Fetal Flow in Europe (TRUFFLE)) performed in 20 European perinatal centers between 2005 and 2010. Women with a singleton fetus at 26–32 weeks of gestation, with abdominal circumference < 10th percentile and umbilical artery Doppler pulsatility index > 95th percentile, were recruited. The main outcome measure was a composite of fetal or neonatal death or severe morbidity: survival to discharge with severe brain injury, bronchopulmonary dysplasia, proven neonatal sepsis or necrotizing enterocolitis. Results Five‐hundred and three of 542 eligible women formed the study group. Mean ± SD gestational age at diagnosis was 29 ± 1.6 weeks and mean ± SD estimated fetal weight was 881 ± 217 g; 12 (2.4%) babies died in utero. Gestational age at delivery was 30.7 ± 2.3 weeks, and birth weight was 1013 ± 321 g. Overall, 81% of deliveries were indicated by fetal condition and 97% were by Cesarean section. Of 491 liveborn babies, outcomes were available for 490 amongst whom there were 27 (5.5%) deaths and 118 (24%) babies suffered severe morbidity. These babies were smaller at birth (867 ± 251 g) and born earlier (29.6 ± 2.0 weeks). Death and severe morbidity were significantly related to gestational age, both at study entry and delivery and also with the presence of maternal hypertensive morbidity. The median time to delivery was 13 days for women without hypertension, 8 days for those with gestational hypertension, 4 days for pre‐eclampsia and 3 days for HELLP syndrome. Conclusions Fetal outcome in this study was better than expected from contemporary reports: perinatal death was uncommon (8%) and 70% survived without severe neonatal morbidity. The intervals to delivery, death and severe morbidity were related to the presence and severity of maternal hypertensive conditions. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.